2016
DOI: 10.4212/cjhp.v69i2.1538
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Heparin Anticoagulation Protocols in Post–Renal Transplant Recipients (EHAP-PoRT Study)

Abstract: Background: Disturbances in hemostasis are common among renal transplant recipients. Because of the risk of thromboembolism and graft loss after transplant, a prophylactic heparin protocol was implemented at St Paul's Hospital in Vancouver, British Columbia, in 2011. Therapeutic heparin is sometimes prescribed perioperatively for patients with preexisting prothrombotic conditions. There is currently limited literature on the safety and efficacy of heparin use in the early postoperative period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…Another study on bleeding risks after perioperative anticoagulation concluded that the utilization of antithrombotic prophylaxis does neither increase the incidence nor the risk for bleeding in the perioperative period, except for postoperative heparin infusion . Heparin infusion, starting within 24 h after surgery, has been associated with an increased risk for bleeding before , as in our analysis, whereas the prophylactic use of heparin (5000 IU s.c. twice daily) is reported to be safe . Others reported an increased risk of bleeding after continued VKA therapy as well, but concluded that the indication for VKA therapy was nonmodifiable in certain patients .…”
Section: Discussionmentioning
confidence: 99%
“…Another study on bleeding risks after perioperative anticoagulation concluded that the utilization of antithrombotic prophylaxis does neither increase the incidence nor the risk for bleeding in the perioperative period, except for postoperative heparin infusion . Heparin infusion, starting within 24 h after surgery, has been associated with an increased risk for bleeding before , as in our analysis, whereas the prophylactic use of heparin (5000 IU s.c. twice daily) is reported to be safe . Others reported an increased risk of bleeding after continued VKA therapy as well, but concluded that the indication for VKA therapy was nonmodifiable in certain patients .…”
Section: Discussionmentioning
confidence: 99%
“…Ng and co-workers evaluated several heparin anticoagulation protocols in the postoperative period after kidney transplantation [ 37 ]. They concluded that the prophylactic use of heparin (5000 IU UFH sc twice daily) is safe.…”
Section: Discussionmentioning
confidence: 99%
“…Data are limited to a few retrospective studies conducted among patients undergoing renal transplantation. 50,51 The majority of those did not report higher incidence of bleeding in patients treated with perioperative heparin prophylaxis at renal transplantation, except one study. 50 In particular, Ng et al 51 recently reported results of the retrospective study on 547 renal transplantations and found bleeding complication in 8 of 266 patients (3%) who received heparin thromboprophylaxis and in 9 of 268 patients (3.4%) who did not.…”
Section: Prophylaxis Of Graft Thrombosis and Early Venous Thromboembomentioning
confidence: 98%
“…In very selected patients with high thrombosis risk, such as patients with aPL, in relation to the estimate of thrombotic risk as previously described, higher heparin dosages can be used when surgical conditions are stable, at least 48 hours after transplantation. In patients at particularly high thrombotic risk, the use of intravenous UFH at therapeutic dosages has been reported by some authors 51,52 ; however, this regimen was associated with an unacceptable high risk of serious bleeding (31-64.3% of cases). The adoption of anticoagulant dosages of heparin in the perioperative period of renal transplantation is associated with a high risk for bleeding and should be limited to highly selected patients, bearing in mind that the occurrence of bleeding complications will determine the temporary contraindication to antithrombotic treatment, exposing the patient also to a prolonged and even higher thrombotic risk.…”
Section: Prophylaxis Of Graft Thrombosis and Early Venous Thromboembomentioning
confidence: 99%
See 1 more Smart Citation